WACANA TEKA-TEKI HUMOR BAHASA INDONESIA: ANALISIS STRUKTUR, ASPEK KEBAHASAAN, DAN FUNGSI - , NUR 'AINI WAHYUNINGSIH, Prof. Dr. I Dewa Putu Wijana, S.U., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
People need humor, but the need is in different levels. Humor does not only serve as entertainment but also as a means of communication and a form of human expression. Humor can take the form of written riddle which is the development of the oral tradition. Its written form is easier to analyze its structure, linguistic aspects and functions. This research is descriptive qualitative with sequence of work steps: data collection, data classification, data analysis, and deduction. Data retrieval is conducted by listening to the data in the form of written humorous riddle discourse of the representative books published in 2010. Furthermore, the data are classified according to certain criteria, and then analyzed. The data analysis uses frontier method to analyze the creation strategy and the function of humorous riddle and agih method to look at the structure facts and language aspects of the humorous riddle. The results of the analysis can be divided into three main points. First, in general, humorous riddle consists of the elements of question and the elements of answer. Humor in the humorous riddle usually arises as a result of the distortion of cooperation principle in communication and in this case it is in the elements of answer. Most of the humorous riddle is created with play techniques, while the remaining is in comparative and opposition tecniques. Second, humorous riddle discourse utilizes language aspects including aspects of phonology, morphology, syntax, semantics, and pragmatics. The use of language aspecs is closely related to human creativity in playing with language to bring out the effect of humor on the riddle. Third, humorous riddle discourse can serve to satirize, ridicule, confuse the readers, disrupt the understanding, and provide entertainment.